2022
DOI: 10.2147/hiv.s372795
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Index Case HIV Testing and Its Associated Factors Among HIV/AIDS Clients on ART Follow-Up in West Ethiopia: A Multi-Centered Facility-Based Cross-Sectional Study

Abstract: Background Index case HIV/AIDS testing (ICHT) is a good approach for addressing and improving the efficiency and yield of testing among high-risk populations. Partners and families of people living with HIV/AIDS are among the high-risk populations for contracting HIV/AIDS. However, there is limited study on index case HIV testing among HIV patients attending Anti-Retroviral Therapy (ART). Hence, this study was aimed at assessing the magnitude and factors associated with ICHT among HIV patients att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
(50 reference statements)
1
8
1
Order By: Relevance
“…In both the unadjusted and adjusted models of the logistic regression analysis, age and marital status emerged as statistically significant factors associated with ICT acceptance. The finding that age is associated with ICT acceptance does not corroborate with previous studies conducted in Tanzania 10 and Ethiopia, 12 which found no association between age and ICT acceptance. The variation observed in these studies could be attributed to cultural differences, sample characteristics, and contextual factors such as environmental or social factors.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In both the unadjusted and adjusted models of the logistic regression analysis, age and marital status emerged as statistically significant factors associated with ICT acceptance. The finding that age is associated with ICT acceptance does not corroborate with previous studies conducted in Tanzania 10 and Ethiopia, 12 which found no association between age and ICT acceptance. The variation observed in these studies could be attributed to cultural differences, sample characteristics, and contextual factors such as environmental or social factors.…”
Section: Discussioncontrasting
confidence: 98%
“…This rate is higher than that of previous studies conducted in Tanzania which reported an acceptance rate of 55.5% 10 but lower than that of a study conducted in Nigeria and Ethiopia that reported an acceptance rate of 84.9% and 85.2% respectively. 11,12 The differences in the acceptance rate among these studies might be due to factors such as effective partner elicitation strategies, the level of awareness about HIV testing and its benefits, stigma and discrimination, fear of being identified as living with HIV and the availability of convenient and confidential HIV testing services. 10 However, it's essential to recognize that further research is warranted to confirm these claims.…”
Section: Discussionmentioning
confidence: 99%
“…Assisted ICT has been widely recognized as an intervention with high potential to increase PLHIV status awareness [6, 13,14,17,19,20,21,22,23,24,25,26,28,29], which is important as countries in eastern and southern Africa strive to reach global UNAIDS targets. This study examines the implementation of assisted ICT from the perspective of very people doing the "assisting."…”
Section: Discussionmentioning
confidence: 99%
“…Traditional approaches to ICT rely on passive referral, in which index clients invite their contacts for testing [6]. However, the World Health Organization (WHO) and the President's Emergency Plan for HIV/AIDS Relief (PEPFAR) have both recommended assisted approaches to ICT [7,8,9], in which health care workers (HCWs) take an active role in referral of at-risk contacts for testing, due to improved effectiveness compared to passive approaches [10,11,12,13,14,15,16,17]. As a result, there have been attempts to scale assisted ICT throughout southern and eastern Africa over the past several years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation